2011
DOI: 10.1007/s11164-011-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

Propane combustion over supported Pt catalysts

Abstract: We prepared Pt catalysts supported on various metal oxides, viz., ZrO 2 , CeO 2 , TiO 2 , yttria-stabilized zirconia (YSZ), SiO 2 , SiO 2 -Al 2 O 3 , and c-Al 2 O 3 , using an incipient wetness method and applied them to propane combustion. In the cases of ZrO 2 -, CeO 2 -, and TiO 2 -supported Pt catalysts, supports with different surface areas were also used. The Pt dispersion in Pt catalysts supported on metal oxides increased with increasing surface area of the support for the same metal oxide. Pt catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This result indicates that the larger Pt particles, which were prepared on supports with a low surface area, are more efficient catalysts for propane combustion than the smaller Pt particles, which were prepared on supports with a high surface area. The results are in agreement with those of a previous report stating that catalysts with small Pt particles exhibited low catalytic activity because of facile oxidation by O 2 [9].…”
Section: Physicochemical Properties Of Catalystssupporting
confidence: 93%
See 2 more Smart Citations
“…This result indicates that the larger Pt particles, which were prepared on supports with a low surface area, are more efficient catalysts for propane combustion than the smaller Pt particles, which were prepared on supports with a high surface area. The results are in agreement with those of a previous report stating that catalysts with small Pt particles exhibited low catalytic activity because of facile oxidation by O 2 [9].…”
Section: Physicochemical Properties Of Catalystssupporting
confidence: 93%
“…To enhance the performance of Pt-based catalysts for low-temperature propane combustion, several factors that affect the catalytic performance have been examined, including the effects of different supports such as Al 2 O 3 , SiO 2 , SiO 2 -Al 2 O 3 , ZrO 2 , yttria-stabilized zirconia, SO 4 2− -ZrO 2 , CeO 2 , MgO, La 2 O 3 , TiO 2 , and zeolites [7][8][9][10][11][12][13][14][15][16][17]. The physicochemical properties of the support reportedly affect the particle size of Pt and the oxidation state of the Pt species, thereby impacting the catalytic activity for propane combustion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The platinum catalysts supported on spinel materials prepared in the present work, as the result of zinc aluminate substitution, show promising performance in the deep propane oxidation and similar or better to that already reported in the literature for other Pt catalysts supported on simple or mixed-metal oxides. Park et al [39] have shown that full conversion temperature (T 100% ) for ∼1 wt.% Pt supported on Al 2 O 3 -SiO 2 , ZrO 2 , CeO 2 and Al 2 O 3 was 200, 275, 300 and 280 • C, respectively, when 1 mol% C 3 H 8 and 5 mol% O 2 in He with flow rate of 100 ml/min were used. Yoshida et al [40] reported the effect of support and additive on Pt catalyst activity in propane combustion showing that T 100% was between 280 and 500 • C, depending on the nature of the support and additive used.…”
Section: Catalytic Properties Of Spinel Supported Pt Catalystsmentioning
confidence: 99%
“…The platinum and palladium catalysts served as a baseline by which to compare catalyst performance. It is well known that the noble metal support affects catalyst performance, 1,8 and tin has been demonstrated to increase the catalytic activity of Pt in CO oxidation. 9 Tin is also an important co-catalyst in propane dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%